Portuguese Guidelines on Multidisciplinary Approach to Obstetric Hemorrhage – Developed by Multidisciplinary Consensus Group 2017 - Carvalhas, Joana; Alves, Cláudia; Tavares Ferreira, Cátia; Santos Silva, Isabel; Costa, Fernando Jorge; Palmira Almeida, Joana; Guedes, Isabel; Aguiar, José; Vilhena, Isabel Rute; Lança, Filipa; et al. (Journal of the Portuguese Society of Anesthesiology, 2018)
These consensuses aim to provide a tool, based on the current scientific evidence, which can have practical applicability and that contributes to the multidisciplinary, transversal and systematic approach, of hemorrhage in obstetrics. They constitute a review of existing recommendations, to facilitate their dissemination and implementation, and to introduce consistency into clinical practice. These guidelines were elaborated, under the sponsorship of the Portuguese Society of Anesthesiology, by a multidisciplinary consensus, between Anesthesiology, Gynecology and Obstetrics, Immunohemotherapy and Hematology experts. Hemorrhage in obstetrics is the leading cause of maternal morbidity and mortality, even in developed countries, but also the most preventable. Postpartum hemorrhage is its most frequent form (5% - 10% of births) and has increased in the last decade. The factors that contribute the most to adverse outcomes are: delayed treatment due to the underestimation of losses, delayed availability of blood products, absence of performance algorithms, insufficient knowledge/training, inadequate interdisciplinary communication and scarce organization. It is essential to identify the risk factors for obstetric hemorrhage. The classic definition of minor postpartum hemorrhage is blood loss > 500 mL after vaginal delivery and > 1000 mL after cesarean section; and major postpartum hemorrhage with losses > 1000 mL. Major postpartum hemorrhage can also be subdivided into moderate (1000-2000 mL) and severe (> 2000 mL), however the American College of Obstetricians and Gynecologists recently revised this definition as ≥1000 mL cumulative blood losses or blood loss accompanied by signs and symptoms of hypovolemia within 24 hours of delivery. This definition comes to meet the definition of massive hemorrhage by the European Society of Anesthesiologists and the Direção Geral de Saúde. All Obstetric Units must have a multidisciplinary institutional protocol for the management of hemorrhage in obstetrics, that should contemplate the early involvement of a multidisciplinary team. This protocol should originate an algorithm, whose objective is to systematize and organize professional and institutional responses, according to the severity of the hemorrhage, in a hands-on concise way. Point-of-care monitoring is recommended for therapeutic guidance and also the possibility of immediate use of tranexamic acid, fibrinogen concentrate and hemostatic balloons. All professionals involved in maternal care should regularly perform multidisciplinary training in obstetric hemorrhage.